Reproductive phenology and morphology of Macrocystis pyrifera (Laminariales, Ochrophyta) from southern New Zealand in relation to wave exposure1. Issue 5 (23rd July 2021) - Leal, Pablo P.; Roleda, Michael Y.; Fernández, Pamela A.; Nitschke, Udo; Hurd, Catriona L.
Abstract : Macrocystis pyrifera is a major habitat forming kelp in coastal ecosystems of temperate regions of the northern and southern hemispheres. We investigated the seasonal occurrence of adult sporophytes, morphological characteristics, and reproductive phenology at two sites within a wave‐protected harbour and two wave‐exposed sites in southern New Zealand every 3–4 months between 2012 and 2013. Seasonality in reproduction was assessed via the number of sporophylls, the occurrence of sori on sporophylls, and non‐sporophyllous laminae (fertile pneumatocyst‐bearing blades and fertile apical scimitars), meiospore release, and germination. We found that M. pyrifera was present and reproductive year‐round in three of the four sites, and patterns were similar for the wave‐exposure conditions. Sori were found on pneumatocyst‐bearing blades and apical scimitars in addition to the sporophylls, and viable meiospores were released from all three types of laminae. Morphological variations between sites with different wave exposure indicate that sporophytes from wave‐protected sites have bigger blades and holdfasts and are longer than those from wave‐exposed sites. We discuss the implications of these biological variables for the ecology of M. pyrifera inhabiting different wave exposure environments in southern New Zealand.